ANALISIS NILAI MORAL DALAM NOVEL “JANJI” KARYA TERE LIYE TAHUN 2021 - Asngadi Rofiq; Milatul Munifah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The result of human imaginative thinking in the form of a literary work with a depiction of the real-life that humans go through itself can be expressed through artistic language. Expressions about human life stories are packaged by writers in beautiful language that is easy for readers to understand. Moral values ??are values ??related to the good and bad of an attitude, and individual behavior in everyday life. A person's moral attitude is motivated by his social life in society, morals are bad or good teachings that are accepted by someone because environmental factors become an act of moral obligation. (Nurgiyantoro, 2015: 429). Based on the results of research that have been carried out regarding the moral values contained in the novel “JANJI” by Tere Liye Tahun 2021, the researchers found 7 aspects of moral values, including Caring for Others with 16 quotes, Helping Helping with 14 quotes, Deliberative aspect 10 quotes, Living in harmony with 9 quotes, the Forgiving aspect 5 quotes, the Right Promise aspect 3 quotes and the Respecting Others aspect 9 quotes. The moral values that exist in the story in the novel make a lesson in dealing with various life problems, how to solve them, and how to apply them to yourself and fellow humans.